2015
DOI: 10.1002/jhm.2407
|View full text |Cite
|
Sign up to set email alerts
|

Variation in readmission rates by emergency departments and emergency department providers caring for patients after discharge

Abstract: BACKGROUND The role of the emergency department (ED) provider and ED facility in readmissions of recently discharged patients who visit the ED has not been studied. OBJECTIVE To determine the variation in readmission rates by ED facility and ED providers caring for patients after discharge. DESIGN Retrospective cohort study using multilevel, multi-variable models of 100% Texas Medicare claims data from the years 2007 to 2011. SETTING Texas acute-care hospitals and ED facilities. PATIENTS Medicare benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
(23 reference statements)
2
10
0
Order By: Relevance
“…The small amount of the total variation in readmission attributable to hospitals, as shown by ICCs, is consistent with previous studies of both readmission 34 and mortality. 35 In addition, Thompson et al 36 concluded that most of the variation for both COPD and HF risk-standardized readmission rates was due to random statistical variation.…”
Section: Discussionsupporting
confidence: 91%
“…The small amount of the total variation in readmission attributable to hospitals, as shown by ICCs, is consistent with previous studies of both readmission 34 and mortality. 35 In addition, Thompson et al 36 concluded that most of the variation for both COPD and HF risk-standardized readmission rates was due to random statistical variation.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of minimal variation in readmission rates by PCP should be taken in the context of our previous research that showed significant variation in risk for readmission by ED physician (10). At the hospital level, overall admission rates are a major determinant of hospital readmission rates (23).…”
Section: Discussionsupporting
confidence: 59%
“…Early follow-up after hospital discharge is sometimes associated with lower readmission rates (8, 9). We previously reported that risk for readmission varies moderately but significantly by ED physician, identifying an opportunity for improvement (10). However, whether PCP care influences readmissions is uncertain, although CMS has implemented a policy incentivizing PCPs to reduce readmissions (11).…”
mentioning
confidence: 99%
“…Variation in performance according to hospital characteristics has been separately described for readmission outcomes, observation care and ED visits. 4,[8][9][10][11][12] For example, large hospitals, teaching hospitals and urban hospitals tend to have slightly higher readmission rates. [13][14][15][16] Whether the types of hospitals with low readmission rates also have low overall post-discharge utilization, however, is uncertain.…”
Section: Introductionmentioning
confidence: 99%